1993
DOI: 10.1161/01.atv.13.6.804
|View full text |Cite
|
Sign up to set email alerts
|

Impaired chylomicron remnant clearance in familial combined hyperlipidemia.

Abstract: Postprandial chylomicron remnant clearance was studied in six patients with familial combined hyperlipidemia (FCH) and seven control subjects by using an oral retinyl palmitate (RP) fat-loading test The chylomicron remnant clearance (S,< 1,000 fraction), expressed as the area under the RP curve (AUC-RP), was delayed in FCH subjects (65.05 ±12.84 hours x [mg/L]) compared with control subjects (25.1±5.4 hoursx[mg/L]; p=0.01). Postprandial lipoprotein particle size and composition in the Sf> 1,000 fraction were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(41 citation statements)
references
References 47 publications
2
38
0
1
Order By: Relevance
“…Heterozygous FH patients are characterized by a partial LOF of the LDLr protein, which is expected to lead to increased circulating plasma TG levels and impaired postprandial handling of dietary fat. In line with previous publications ( 13,34,35 ), we found that plasma TG levels and postprandial TG clearance is indeed impaired in heterozygous FH patients as compared with the controls, illustrating the role for the LDLr in remnant clearance ( 36 ). However, the increase in plasma TG levels is only modest, confi rming earlier reports showing minor TG elevations in FH homozygous patients ( 37 ).…”
Section: Trl Clearance In Fhsupporting
confidence: 92%
“…Heterozygous FH patients are characterized by a partial LOF of the LDLr protein, which is expected to lead to increased circulating plasma TG levels and impaired postprandial handling of dietary fat. In line with previous publications ( 13,34,35 ), we found that plasma TG levels and postprandial TG clearance is indeed impaired in heterozygous FH patients as compared with the controls, illustrating the role for the LDLr in remnant clearance ( 36 ). However, the increase in plasma TG levels is only modest, confi rming earlier reports showing minor TG elevations in FH homozygous patients ( 37 ).…”
Section: Trl Clearance In Fhsupporting
confidence: 92%
“…However, the uptake of LDL, albeit oxidized, by 3T3-L1 adipocytes was reported to increase cell proliferation and decrease cell differentiation (21)(22)(23). Moreover, multiple clinical studies have demonstrated that statin therapy, which reduces plasma concentrations of apoBlipoproteins, also improves plasma clearance of triglyceride (TG) (24)(25)(26)(27). Therefore, it is possible that elevated concentrations of apoB-lipoproteins not only are a consequence of dysfunctional WAT and hypertriglyceridemia but also play an active role in their pathology.…”
Section: Postprandial In Vivo Fat Clearancementioning
confidence: 99%
“…Today, it is commonly accepted that the increased plasma triglycerides, total cholesterol, and apoB in FCHL are heterogeneous in origin, because they are the consequences of both an overproduction of VLDL particles and a decreased clearance of remnants (12)(13)(14). Therefore, researchers have stated that lipid levels are not the optimal phenotypical markers for elucidating the genetic background of FCHL (15).…”
mentioning
confidence: 99%